CHARACTERISTICS OF MORAL AND SPIRITUAL PREPARATION OF CADETS OF HIGHER MILITARY EDUCATIONAL INSTITUTIONS - Khasanboev, Bekzod (Журнал иностранных языков и лингвистики, 2023)
In this article, in the process of theoretical and practical training in the organization of moral-spiritual training of future officers in their professional activities, correct mental and physical actions in real and tense situations related to non-standard decision-making, quick adaptation and independent action in complex situations, personnel management, Aspects of using professional-psychological training for future officers depending on their specialty in raising the fighting spirit, leading them, and organizing psychological training are highlighted.